Genotype – Phenotype Correlations of β-Thalassemia Mutations in Azerbaijani population - Asadov, Chingiz; Abdulalimov, Eldar; Mammadova, Tahira; Gafarova, Surmaya; Guliyeva, Yegana; Aliyeva, Gunay (Turkish journal of haematology, 2017)
β-Thalassemia is the most common inherited disorder in Azerbaijan. The aim of our study was to reveal genotype-to-phenotype correlations of the most common β-thalassemia mutations in an Azerbaijani population. Patients with codon 8 (-AA), IVS-I-6 (T>C), and IVS-II-1 (G>A) mutations, which are reportedly the most common β-globin gene mutations among the local population, were tested for hematologic parameters. Fifty-five previously tested patients with known genotypes were included in the study. Hematologic indices and hemoglobin fractions were tested in order to reveal the phenotypic manifestation of the mutations. The results obtained indicate that clinical presentation varies between different β-globin gene mutations: individuals with IVS-I-6 (T>C) mutations showed milder presentation than those with codon 8 (-AA) and IVS-II-1 (G>A), which is associated with the molecular basis of the mutations. These data can be of assistance to predict clinical presentation and select the best possible therapeutic approach via early genotype identification.